Biotechnology: A Panacea to Climate Change Disasters- Brief Review - Emmanuel, Ekpa; Amina Bature, Shehu; Erika Nancy, Micheal; Muhibat, Komolafe; Madinat, Hassan (Journal of Weather Changes, 2022)
Man’s activity and/ or inactivity continually impedes the environment in many ways. Sometimes, these impediments could be negative with catastrophic consequences. Emission of greenhouse gases, desert encroachment, deforestation, global warming, and general environmental degradation by different human practices poses a lot of threat to this planet. It has therefore become imperative to explore novel ways or technologies in checkmating hazards emanating from these disasters. Biotechnology which simply refers to the use of living organisms or their parts particularly microorganisms to produce materials for human and animal consumption comes in handy. The aim of this paper is to do a brief review on the merits of applying this technology in mitigating hazards arising from climate change. Focus will be centered on agricultural and industrial biotechnology more as a result of their involvement in land and environmental related matters. Manipulation of crops via genetic engineering for varieties with stress resistance, phytoremediation, tissue culture of orphan crops, and so many other biotechnological practices will be examined so as to highlight their role in stemming disasters caused by climate change. In conclusion, the paper will attempt to explain the reason why developing countries like Nigeria should also join the global race in curtailing this menace via her indigenous biotechnology.
Keywords: Climate Change; Biotechnology; Environmental degradation; Nigeria